2017
DOI: 10.1002/yea.3230
|View full text |Cite
|
Sign up to set email alerts
|

Emodin, a natural inhibitor of protein kinase CK2, suppresses growth, hyphal development, and biofilm formation of Candida albicans

Abstract: Emodin (1,3,8-trihydroxy-6-methyl-anthraquinone) is a natural secondary plant product, originally isolated from the rhizomes of Rheum palmatum. Many reports show its diuretic, vasorelaxant, antibacterial, antiviral, anti-ulcerogenic, immunosuppressive, hepatoprotective, anti-inflammatory and anticancer potential. Emodin is a pleiotropic molecule capable of interacting with several major molecular targets, e.g. NF-κB, AKT/mTOR and STAT3. The compound can also act as an inhibitor of some protein kinases, with sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 51 publications
4
46
0
Order By: Relevance
“…The in vitro antimicrobial study was performed using the microbroth dilution method against tested organisms, followed by a previously described method ,. The bacterial culture was inoculated in Mueller Hinton Broth medium (Biocorp, Warsaw, Poland) and incubated at 37 °C and with vigorous shaking (200 rpm) for 24‐h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro antimicrobial study was performed using the microbroth dilution method against tested organisms, followed by a previously described method ,. The bacterial culture was inoculated in Mueller Hinton Broth medium (Biocorp, Warsaw, Poland) and incubated at 37 °C and with vigorous shaking (200 rpm) for 24‐h.…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro antimicrobial study was performed using the microbroth dilution method against tested organisms, followed by a previously described method. [37,38] The bacterial culture was inoculated in Mueller Hinton Broth medium (Biocorp, Warsaw, Poland) and incubated at 37°C and with vigorous shaking (200 rpm) for 24h. Bacterial cell suspensions at initial inoculums of 5 × 10 5 in Mueller-Hinton liquid medium were exposed to the examined compounds at relevant concentrations (range, 0.001-2 mg/mL) for 24-h at 37°C.…”
Section: In Vitro Antibacterial Activitymentioning
confidence: 99%
“…The ability to adhere to host tissues has been described in all species of the Candida genus, but in comparison with C. albicans, C. tropicalis, and C. parapsilosis, lower adhesive properties have been detected in C. glabrata [6,15]. In the recent years, many efforts have been made to explore new and effective natural compounds with anti-adhesion and anti-biofilm development effects [7,[16][17][18]. Tests As demonstrated in previous studies on natural compounds, phenols such as flavonoids and lignans have shown their antimicrobial potential [7].…”
Section: Resultsmentioning
confidence: 99%
“…Candida albicans is a common, opportunistic human fungal pathogen that can cause both mucosal and deep tissue infections (Janeczko, Maslyk, Kubinski, & Golczyk, 2017), and is the most frequently isolated fungus from clinical settings (Leite, de Brito Bezerra, de Sousa, & de Oliveira Lima, 2015). C .…”
Section: Introductionmentioning
confidence: 99%
“…albicans inhabits the body as a commensal, but during immunosuppression, it is the causative agent of human candidiasis (Lopez‐Martinez, 2010) and can also cause including potentially life‐threatening blood‐borne infections. The Candida genus includes about 20 different Candida species that are known to be etiological agents of human infections (Janeczko et al, 2017), and many fungal species are developing resistance to commonly prescribed antifungal agents (Ellis, 2002). The threat from Candida species is especially serious in immunocompromised patients, including organ transplant recipients, patients receiving cancer radiotherapy or chemotherapy, and HIV/AIDS patients (Leite et al, 2015).…”
Section: Introductionmentioning
confidence: 99%